2016
DOI: 10.1371/journal.pone.0150711
|View full text |Cite
|
Sign up to set email alerts
|

Insight on Genes Affecting Tuber Development in Potato upon Potato spindle tuber viroid (PSTVd) Infection

Abstract: Potato (Solanum tuberosum L) is a natural host of Potato spindle tuber viroid (PSTVd) which can cause characteristic symptoms on developing plants including stunting phenotype and distortion of leaves and tubers. PSTVd is the type species of the family Pospiviroidae, and can replicate in the nucleus and move systemically throughout the plant. It is not well understood how the viroid can affect host genes for successful invasion and which genes show altered expression levels upon infection. Our primary focus in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
36
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 51 publications
9
36
0
2
Order By: Relevance
“…The increasing evidence suggests that overexpression of the MED subunits' genes elevates the expression of their immediate target genes [36]. The elevated and tailored expression of the MED subunits observed in our study, coupled with several previous reports about the massive modulation of genes involved in immune responses, primary and secondary metabolism and hormone signalling pathways [30,[37][38][39], provided circumstantial support for the prominent role of the MED complex in the orchestrated transcriptional reprogramming of host genes in response to viroid infection. and hop (C) plants.…”
Section: Resultssupporting
confidence: 83%
“…The increasing evidence suggests that overexpression of the MED subunits' genes elevates the expression of their immediate target genes [36]. The elevated and tailored expression of the MED subunits observed in our study, coupled with several previous reports about the massive modulation of genes involved in immune responses, primary and secondary metabolism and hormone signalling pathways [30,[37][38][39], provided circumstantial support for the prominent role of the MED complex in the orchestrated transcriptional reprogramming of host genes in response to viroid infection. and hop (C) plants.…”
Section: Resultssupporting
confidence: 83%
“…Similarly, HSP (HSP70 and HSP90) family homologs were shown to be induced several folds in many plant interaction studies with RNA viruses and viroids [74,75]. AP2/EREBP and ERFs were significantly altered in CBCVd-infected plants (Table S3), which is consistent with results of previous study of PSTVd-infection in potato [78]. Nodes in different colour "red" and "green" indicate the up-and down-regulation of genes, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…On the other hand, it is known that viroids can inactivate some transcription factors, including EREBP, usually by suppressing regulation ways of mRNA associated with them (Matoušek et al, 2015;Katsarou et al, 2016). In this research, no differences were found in EREBP expression.…”
Section: Palabras Clave: Avocado Sunblotch Viroid Persea Americana mentioning
confidence: 51%
“…Por otro lado, se sabe que los viroides pueden inactivar algunos factores de transcripción, incluyendo EREBP, generalmente al suprimir las vías de regulación de los mRNA asociados a ellos (Matoušek et al, 2015;Katsarou et al, 2016). En esta investigación no hubo diferencias en la expresión de EREBP.…”
Section: Palabras Clave: Avocado Sunblotch Viroid Persea Americana unclassified